1990
DOI: 10.1093/brain/113.2.397
|View full text |Cite
|
Sign up to set email alerts
|

Semantic Memory Loss in Dementia of Alzheimer's Type

Abstract: This paper examines three methodological issues concerning the measurement of semantic memory impairment in brain-damaged patients. Ten carefully selected patients with dementia of Alzheimer's type (DAT) and anomia were studied. A battery of perceptual tests and direct tests of semantic memory led to the conclusion that these patients represented a homogeneous group having a prominent deterioration of their semantic memory store without visual perceptual deficits. The first issue addressed in this patient grou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

20
294
5
26

Year Published

1993
1993
2016
2016

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 517 publications
(345 citation statements)
references
References 49 publications
20
294
5
26
Order By: Relevance
“…In a seminal study, Chertkow and Bub (1990) used an item-to-item specific test and observed error consistency across test trials, providing support for the degraded store view. In this study, the patients were first asked to name pictures and subsequently to perform a "same category word to picture matching" task.…”
Section: Introductionmentioning
confidence: 96%
“…In a seminal study, Chertkow and Bub (1990) used an item-to-item specific test and observed error consistency across test trials, providing support for the degraded store view. In this study, the patients were first asked to name pictures and subsequently to perform a "same category word to picture matching" task.…”
Section: Introductionmentioning
confidence: 96%
“…Impairment in delayed recall seems to be one of the best predictors of future dementia (Small et al, 2000;Ivanoiu et al, 2005). Semantic memory, which concerns general world knowledge, is also impaired in AD, even at the pre-dementia stages of the disease (Chertkow and Bub, 1990;Duong et al, 2006;Joubert et al, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…Semantic deficits have been documented in AD using a variety of standard clinical neuropsychological tests (Huff et al, 1986;Rosser and Hodges, 1994;Hodges and Patterson, 1995;Adlam et al, 2006) and using more specific measures (Chertkow and Bub, 1990;Hodges et al, 1992;Greene and Hodges, 1996;Fung et al, 2001;Thompson et al, 2002;Whatmough et al, 2003;Joubert et al, 2010). Working memory deficits are also frequently reported in AD and involve reduced span for words, digits, letters and spatial locations (Grossi et al, 1993;Belleville et al, 1996).…”
Section: Introductionmentioning
confidence: 99%
“…Compared with normal subjects, AD patients generate significantly fewer members of common semantic categories (Canning et al, 2004;Graham et al, 2004;Lipton et al, 2003, Monsch et al, 1994Salmon et al, 1999), a result either of the loss of semantic information or its disorganization (e.g., Chertkow & Bub, 1990;Grober et al, 1985;Martin & Fedio, 1983).…”
Section: Animal Fluencymentioning
confidence: 99%